Interface passivation using choline acetate for efficient and stable planar perovskite solar cells - Thambidurai, Mariyappan (2023)
In order to enhance the efficiency and robustness of perovskite solar cells (PSCs), surface passivation is crucial to minimize surface defects, improve charge transfer, and inhibit the penetration of deteriorating agents. In this study, we demonstrate that choline acetate (ChAc) can effectively passivate the surfaces of perovskites to improve their stability and photovoltaic performance. The perovskite film passivated with ChAc shows many improvements, such as greater crystallinity, smoother surface topography, preferable alignment of energy levels, and lower defect density. As a result, the champion power conversion efficiency (PCE) for the pristine and ChAc PSCs is 18.20% and 19.80%, respectively. The passivated PSCs also display superior stability, as evidenced by retained unencapsulated PCE of 93% after 600 hours of storage at ambient conditions and 40% relative humidity at 25 °C, compared to 85% retained for pristine PSCs. Our results provide a straightforward and very efficient way to produce high-performing and stable PSCs.